Developing an Adaptive Resilience Index for Flood-Resistant Urban Drainage Systems - Emma Louise; Hiroshi Takeda (Universitas Sains dan Teknologi Komputer, 2025)
Most urban drainage systems worldwide are under unprecedented stress due to extreme weather driven by climate change and rapid urbanization. This creates severe challenges for traditional static design paradigms. While the different resilience indices proposed to date provide useful performance benchmarks, they reflect the system state at a single point in time and do not capture the system’s dynamic capacity to adapt and learn under evolving climatic pressures and urban growth. This paper helps fill this research gap by introducing a new conceptual framework, the Adaptive Resilience Index (ARI). ARI integrates three core dimensions: System Capacity, Climatic Sensitivity, and Adaptive Capacity, offering a potential framework for assessing adaptive resilience in urban drainage systems. The tripartite structure provides a dynamic lens to evaluate system robustness, vulnerability to climatic shifts, and proactive capacity for learning and reorganization. Although the ARI has not yet been empirically tested, its proposed indicators could be operationalized in future studies through surveys, modeling, and institutional assessments, thereby guiding the development of more resilient, adaptive, and sustainable urban drainage infrastructure in a climate-uncertain world.